(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mainly hybrid cows, native cows, village milk cows and milk buffaloes are reared for dairy business. If this business is done commercially with modern techniques than doing dairy business in the traditional way, it is definitely a sustainable business, financially affordable and good income. Animal husbandry provides many non-commercial economic benefits, including the use of farmyard manure as fuel or organic fertilizer. Manure is the sole source of nutrients for crop production in many farming systems. As the population of the cities increased, the traders who bought milk from the rural people and supplied it to the urban population started getting involved in the dairy business. These poor people started buying milk at a very low price and selling it to the city dwellers at an inflated price with a huge profit. The demand for milk increased and the price also got better. However, this did not fetch the original milk produced a fair price.